2002
DOI: 10.1007/s00425-002-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of caspase-like proteases and induction of apoptosis by isopentenyladenosine in tobacco BY-2 cells

Abstract: The effects of isopentenyladenosine (iPA) on tobacco (Nicotiana tabacum L.) BY-2 cells were examined. The number of BY-2 cells decreased in a time- and concentration-dependent manner after being exposed to micromolar concentrations of iPA. This decrease was mainly due to a loss of cell viability, since no substantial changes in cell cycle progression were revealed by flow-cytometric analysis. Dying cells exhibited the typical morphological and biochemical hallmarks of apoptosis, including cell shrinkage, chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
2
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 43 publications
4
57
2
3
Order By: Relevance
“…Other forms of PCD in N. tabacum, including those induced by bacteria (Richael et al, 2001) and treatment with a fungal elicitor (Elbaz et al, 2002), also were prevented by caspase inhibitors. Similar results were obtained with caspase inhibitors in preventing or reducing cell death after treatment with camptothecin (De Jong et al, 2000), staurosporine (Elbaz et al, 2002), and isopentenyladenosine (Mlejnek and Prochá zka, 2002). In addition, heat shock-induced PCD in N. tabacum suspension cells stimulated cleavage of PARP and activation of a caspase-3-like protease (Tian et al, 2000), whereas N. tabacum protoplast treated with menadione displayed PARP cleavage (Sun et al, 1999).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Other forms of PCD in N. tabacum, including those induced by bacteria (Richael et al, 2001) and treatment with a fungal elicitor (Elbaz et al, 2002), also were prevented by caspase inhibitors. Similar results were obtained with caspase inhibitors in preventing or reducing cell death after treatment with camptothecin (De Jong et al, 2000), staurosporine (Elbaz et al, 2002), and isopentenyladenosine (Mlejnek and Prochá zka, 2002). In addition, heat shock-induced PCD in N. tabacum suspension cells stimulated cleavage of PARP and activation of a caspase-3-like protease (Tian et al, 2000), whereas N. tabacum protoplast treated with menadione displayed PARP cleavage (Sun et al, 1999).…”
Section: Introductionsupporting
confidence: 70%
“…Because caspases can play such a critical role in the process and because numerous experiments have shown that caspase-specific inhibitors prevent Silver stained gel of purified SAS-1 and SAS-2; 15 mL of active fraction was loaded per lane. some forms of PCD in plants (del Pozo and Lam, 1998;Sun et al, 1999;Tian et al, 2000;Richael et al, 2001;Elbaz et al, 2002;Mlejnek and Prochá zka, 2002), it has been speculated that proteases similar to caspases are involved in plant PCD. We have purified and characterized two subtilisin-like Ser proteases that possess specificity for caspase-specific substrates and inhibitors and apparently participate in a signaling cascade involving multiple proteases, leading to the proteolysis of Rubisco.…”
Section: Discussion Pcd and A Protease Cascadementioning
confidence: 99%
“…However, leaves of cytokinindeficient engineered transgenic Arabidopsis plants show a delay of senescence, rather than an acceleration (Werner et al 2001, Werner et al 2003. On the other hand, cytokinins reportedly induce PCD in plants, including tobacco (Mlejnek and Prochazka 2002), carrot and Arabidopsis (Carimi et al 2003). Additionally, Carimi et al (2004) reported that in Arabidopsis cell suspension cultures, high levels of BAP induce features of PCD by accelerating senescence and in carrot cells, high levels of BAP and carbanilide, another cytokinin, induce some features of PCD, but kinetin and zeatin, which are also cytokinins, do not.…”
Section: Resultsmentioning
confidence: 99%
“…Salicylic acid, a hormone involved in the pathogen response, also modifies the auxin response . Abnormal cytokinin levels are equally monitored by plants, and unusually high concentrations of cytokinin can induce programmed cell death (Carimi et al, 2003;Mlejnek and Prochazka, 2002) and the expression of the pathogen resistance gene PR1 (Memelink et al, 1987).…”
Section: Moving Transcriptional Regulators Mediate Shortand Long-rangmentioning
confidence: 99%